Analysis of Financial Technology Business Innovation: A Case Study of Bank Jago - Nurshary, Raisa (Enigma in Economics, 2024)
Bank Jago has developed various innovative digital products and services, such as Jago Invest, Jago Autopilot, and Jago Community. These products and services are designed to meet the needs and lifestyle of the modern and digital Indonesian people. Development of sophisticated technological infrastructure. Bank Jago has invested in developing advanced technological infrastructure, such as cloud computing and artificial intelligence. This sophisticated technological infrastructure allows Bank Jago to provide innovative and safe products and services. Development of quality digital talent. Bank Jago has invested in developing quality digital talent, through training and development programs. This quality digital talent is important for developing innovative digital products and services. Collaboration with various partners. Bank Jago has collaborated with various partners, both from the financial and non-financial industries, to develop its products and services. This collaboration is carried out to expand access and benefits of Bank Jago products and services to the Indonesian people.